An Unusual Case of Vaccine-Associated Paralytic Poliomyelitis - S Desai; T Diener; BJ-K Tan; NJ Lowry; C Talukdar; WM Chrusch; S Wiebe (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present article reports a case involving an immunocompetent, previously well child who, despite two previous doses of inactivated poliovirus vaccine, developed severe flaccid paralysis consistent with polio after receiving oral polio vaccine.